Childhood government in contemporary Brazil: mutations - Gallo, Silvio (2021)
This paper works with the idea that childhood has no perspective of emancipation, due its guardianship by the adults. This is supported by René Schérer’s philosophy of childhood. The paper investigates the childhood government in contemporary Brazil. Presents the hypothesis that it was produced, since the end of the military government, in 1985, a “democratic governmentality” sustained by the Foucault’s concept of governmentality. The children are taken as “subjects of rights” and governed as citizenships. It means another way of guardianship. Public policies in Education are mobilized to sustain the hypothesis. Some changes can be seen since 2016 in the Brazilian childhood government and the article concludes with interrogations about these mutations.